Stability of stainless steel (SS), cobalt crome (CO/CR) and B-Titanium lingual archwires - Cheshankova-Kostova, Elena L. (My University, 2014)
This study investigated the stability of archwires used as lower lingual retainers in orthodontics. Straight 90 mm lengths ofSS, Co/Cr (Elgiloy “blue”) of 0.036" and 0.040" diameter and p-Titanium (TMA) of 0.036" orthodontic wires were bent into a standard lingual arch form. The SS was heat-treated at 900° F for 10 minutes and the Co/Cr at 1200° F for five minutes in a dental furnace. The (3-Titanium and the SS and Co/Cr control groups were not heat-treated. Arch widths were measured immediately after heat-treatment, at four and at eight weeks later. Heat-treatment produced an immediate expansion, especially in the SS (0.036" by 4.91 mm; 0.040" by 4.19 mm). Little change was recorded thereafter, with Elgiloy 0.036" and 0.040" being the most stable. When the arches which had not been heat-treated were measured the Elgiloy 0.036" recorded the greatest change (0.853 mm) after eight weeks. The forces generated when the expanded arches were compressed to their original contour were of rather small levels. The 0.036" Elgiloy offered the greatest force (14.0102 grams). The remaining arches recorded force levels ranging from 3.0612 grams to 11.0918 grams. Statistical analyses included an Anova test which revealed statistical significance for several of the changes at a probability level of 0.0001. However, the quanta of the forces generated were of levels unlikely to have any clinical impact. The experiment indicated that heat-treating wires used for lingual arches was probably not indicated in the clinical application.
Thesis (M.Sc.(Dent.))--University of the Witwatersrand, Faculty of Health Sciences, 1999.